The Werewolf - Kris Hirschmann
Werewolves are part human, part wolf, and all awful. This book examines these legendary creatures in frightening detail, describing their bodies, their behavior, and their monstrous transformations. It also goes snout to snout with some of history's most infamous real-life werewolves and discusses the many books and films these encounters have inspired. These fictional portrayals, along with the werewolf's countless contributions to popular culture, are proof (3z(Bpawsitive(3y (Bof this ancient monster's modern appeal.s